Perencanaan Kehamilan dan Harapan Persalinan pada Ibu Hamil Remaja - Rahmawati, Veronica Yeni (KOSALA : Jurnal Ilmu Kesehatan, 2019)
Adolescent mothers have different psychological condition in facing childbirth. This study to identify a correlation between planning of pregnancy and childbirth expectation of adolescent mothers in Indonesia. This cross-sectional study applied a consecutive sampling. The sample was 135 adolescent mothers. Instruments utilized were structured questionnaire, including a demographic questionnaire, London Measure of Unplanned Pregnancy (LMUP) and Childbirth Expectation Questionnaire (CEQ). All questionnaires were in Indonesian version. The correlation of planning of pregnancy and childbirth expectation was analyzed using chi-square. The results showed a significant correlation between planning pregnancy and childbirth expectation of adolescent mothers OR=2,5; (p=0,006) 95% CI 2,126-7,544. An important factor to increase childbirth expectation of adolescent mothers is the planning of pregnancy. Special assistance for adolescent mothers after married is necessary to decide about planning of pregnancy. Keywords : childbirth expectation, planning of pregnancy, adolescent mothers